Draft Annual Plan 1988-89 (Sub-Plan) (i) Leh (ii) Kargil (iii) Gujjar and Bakerwal Jammu and Kashmir - Planning Commission (Planning Commission, 1987)
An outlay of Rs. 4590.00 lakhs has been provided to district Leh for implementation of various developmental schemes during the Seventh Five Year Plan. The cumulative expenditure during 1985-86 and 1986-87 was of the order of Rs. 195.90 lakhs including Rs. 50.00 lakhs provided under upgradation programme. The anticipated expenditure for the year, 1987-88 is Rs. 1200.48 lakhs against the approved outlay of Rs. 1107.00 lakhs including Rs. 40.60 lakhs provided under the upgradation programme. The outlay proposed for 1988-89 is of the order of Rs. 1257.00 lakhs including Rs. 2037 lakhs for upgradation programme.
Planning and Development Department, Jammu and Kashmir